Factors Affecting Revenue Management In The Registered Food And Beverage Sector Of The Indonesian Stock Exchange - Afrizal Sofyan Lubis*; Hamdy Hady; Febria Nalurita (Riwayat: Educational Journal of History and Humanities, 2023)
This study's objective was to investigate the corporate governance, company performance, and corporate social responsibility factors that influence earnings management in the food and beverage sector listed on the Indonesia Stock Exchange. This study employs an exploratory descriptive approach to identify indications of the impact of corporate governance, corporate performance, and corporate social responsibility on corporate earnings management. The research sample comprises as many as 34 food and beverage manufacturing companies. This study employs panel data regression for its data analysis method. Using E-Views 10.0, the available data was examined. Results indicated there was no effect of corporate governance on firm performance, no effect of corporate governance on earnings management, an effect of corporate responsibility on corporate responsibility, a negative effect of firm performance on earnings management, a positive influence of corporate responsibility on earnings management, and a negative effect of corporate governance on earnings management that was statistically significant. Implications of the research: corporate governance should focus on earnings management by evaluating company performance, corporate governance, and corporate responsibility. This study can be used as a foundation for developing prior research in order to obtain empirical evidence regarding the factors that influence earnings management.